2017
DOI: 10.3389/fcimb.2017.00130
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Mediated by Toll-Like Receptor 5 Sensing of Pseudomonas aeruginosa Flagellin Influences IL-1β and IL-18 Production by Primary Fibroblasts Derived from the Human Cornea

Abstract: Pseudomonas aeruginosa is the principal cause of bacterial keratitis worldwide and overstimulation of the innate immune system by this organism is believed to contribute significantly to sight loss. In the current study, we have used primary human corneal fibroblast (hCF) cells as an ex vivo model of corneal infection to examine the role of P. aeruginosa flagellum and type three secretion system (TTSS) in inducing inflammasome-associated molecules that trigger IL-1β and IL-18 production during the early stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
0
19
2
Order By: Relevance
“…Recently, we have shown with adherence and gentamicin exclusion assays that P. aeruginosa can adhere to primary hCFs and subsequently invade ( Cendra et al, 2017 ). In the current study, MOI-dependent levels of PAO1 adherence and subsequent invasion were observed after 3 h of infection ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have shown with adherence and gentamicin exclusion assays that P. aeruginosa can adhere to primary hCFs and subsequently invade ( Cendra et al, 2017 ). In the current study, MOI-dependent levels of PAO1 adherence and subsequent invasion were observed after 3 h of infection ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Infection of hCFs with P. aeruginosa PAO1 induces significant extracellular release of the cytokine IL-1β ( Wong et al, 2011 ; Cendra et al, 2017 ). Since exacerbation of the inflammatory response is a critical event during eye infection, we tested the hypothesis that antibiotic treatments not only reduced bacterial infection but were also anti-inflammatory, by influencing IL-1β cytokine production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the production of pro-IL-1β and pro-IL-18 can be influenced by TLR5 signaling. 12 These observations may explain why reduced TLR5 activity was accompanied by decreased NLRC4 signaling in aa 89-96 fliC → flaA mutant flagellin.…”
mentioning
confidence: 97%